A Retrospective Study of 199 Xen45 Stent Implantations From 2014 to 2016. Issue 1 (January 2019) - Heidinger, Astrid; Schwab, Christoph; Lindner, Ewald; Riedl, Regina; Mossböck, Georg
Abstract : Purpose: The aim of this study is to determine the postoperative course after Xen45 Gel Stent implantation at the Medical University of Graz from 2014-2016. Methods: Single-center, retrospective study. All patients with Xen implantation between 2014 and 2016 were included. Clinical records and reports received from supervising ophthalmologists were used for evaluations. Investigated parameters were intraocular pressure (IOP), the number of medications, visual acuity, and the number of previous operations, IOP-follow-up, intraoperative and postoperative complications, the rate of interventions (needling), and additionally performed surgeries. Results: Xen was implanted in 199 eyes of 160 patients. Mean preoperative IOP was 22.8±6.9 mm Hg on 2.9±1.0 IOP-lowering medication. After 12 months follow-up, mean IOP was 17.1±5.9 mm Hg (n=89, P <0.0001; mean reduction of 22.7%) on 1.8±1.4 (n=87; P <0.0001) IOP-lowering medications. There were no intraoperative complications and in two cases (1.0%) severe postoperative adverse events occurred (aqueous misdirection and late-onset endophthalmitis). Postoperative needling was indicated in 44 cases (22.1%), while in 28 cases (14.1%) an additional glaucoma surgery was performed. Conclusions: Our results indicate that Xen implantation is an effective surgical intervention leading to a significant reduction of IOP and number of medications with a low rate of complications. An attentive postoperative management seems to be mandatory. Abstract : Supplemental Digital Content is available in the text.